2016
DOI: 10.1007/s11214-016-0260-5
|View full text |Cite
|
Sign up to set email alerts
|

Solar Coronal Jets: Observations, Theory, and Modeling

Abstract: Coronal jets represent important manifestations of ubiquitous solar transients, which may be the source of significant mass and energy input to the upper solar atmosphere and the solar wind. While the energy involved in a jet-like event is smaller than that of "nominal" solar flares and coronal mass ejections (CMEs), jets share many common properties with these phenomena, in particular, the explosive magnetically driven dynamics. Studies of jets could, therefore, provide critical insight for understanding the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
299
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(318 citation statements)
references
References 202 publications
18
299
0
1
Order By: Relevance
“…Depending on their morphology, solar jets have been recently divided into two categories, standard and blowout (or erupting) jets (Raouafi et al 2016). With their peculiar untwisting motion, blowout jets are still not well understood.…”
Section: Introduction Particle Acceleration In Solar Flaresmentioning
confidence: 99%
“…Depending on their morphology, solar jets have been recently divided into two categories, standard and blowout (or erupting) jets (Raouafi et al 2016). With their peculiar untwisting motion, blowout jets are still not well understood.…”
Section: Introduction Particle Acceleration In Solar Flaresmentioning
confidence: 99%
“…Coronal jets are transient collimated features (Raouafi et al 2016) typically observed in extreme ultraviolet (EUV) (Wang et al 1998) and X-ray (Shibata et al 1992;Canfield et al 1996;Alexander & Fletcher 1999) emission. They occur in different solar environments over a broad range of temporal and spatial scales (Cirtain et al 2007;Moore et al 2010;Innes et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They are most often detected as rapidly evolving linear features in which plasma appears to be accelerated and sometimes heated, with the bulk of the plasma flow often penetrating into the overlying and much hotter corona. There is a wide variety of chromospheric jets, including surges, penumbral microjets, anemone jets, macrospicules, and spicules (Raouafi et al 2016). To fully understand the impact of these different jets on the mass and energy balance of the low solar atmosphere, it is key to better understand the mechanisms that drive these jets.…”
Section: Introductionmentioning
confidence: 99%